Mass Mapping the Cosmic Web: Insights from Redshift Dispersions in Supercluster Filaments - Goshu, Belay Sitotaw (Budapest International Research and Critics University, 2026)
Understanding the large-scale structure of the universe, including galaxy clusters and filaments, is essential for advancing our knowledge of cosmic evolution. Redshift distributions and mass-velocity dispersion relations are key observational metrics used to study these structures. The simulations provide a valuable tool for replicating and understanding the dynamics of galaxies across different environments, but discrepancies between observed and simulated data. This work examines and analyzes the redshift distributions and mass-velocity dispersion relations of clusters and filaments. The goal is to evaluate the degree to which simulations accurately depict visible large-scale cosmic structures and identify areas that require development. It analyzed observed and simulated data for redshift distributions and mass-velocity dispersion relations in galaxy clusters and filaments. Statistical methods were used to compute the main parameters, including means, standard deviations, and correlation coefficients. Moreover, comparisons of log-log slopes between observed and simulated mass-velocity dispersion relations were conducted. While simulations effectively captured mass-velocity dispersion trends, significant differences in redshift distributions were observed, indicating gaps in the simulation's ability to model smaller-scale structures. These discrepancies highlight limitations in the current simulation models, particularly in accounting for non-gravitational forces. The results show that simulations closely match observed mass-velocity dispersion trends. However, the accurately reproduced observed redshift distributions have some limitations. According to the study, improving filament modeling and fine-tuning filament physics may increase simulation accuracy. The intricacy of filament dynamics is indicated by the weak association between velocity dispersions and filament mass.